Preparation and Characterization of Activated Carbon from Waste Sawdust from Saw Mill - Shrestha, Dibyashree; Gyawali, Gobinda; Rajbhandari, Armila (Journal of Institute of Science and Technology, 2018)
Activated carbon was prepared in laboratory using waste sawdust powder of Shorea robusta (Sal) from saw mill by chemically activated Na2CO3 followed by carbonization technique. Thus prepared activated carbon was characterized by Iodine Number (IN) and Methylene Blue Number (MBN). Iodine number was found to be 534.6 mg/g whereas MBN was found to be 196.08 mg/g which indicated the presence of micropores as well as mesopores in the prepared material. This was also exposed by SEM image. Specific surface area was measured by BET method and was found to be 10.01 m2/g. Then phase state of samples was determined by X-ray diffraction (XRD), which indicated the amorphous nature of the prepared material. The development of surface functionality due to activation was examined by Fourier Transform Infrared Spectroscopy (FTIR) which showed the presence of oxygenated functional groups such as ether, diketone, lactone, phenol on the material. These functional groups are considered to be electrochemically active and contribute to the capacitance of electrical double layer capacitance (EDLC). Further, electrochemical characterization of prepared material was carried out by conductivity test and cyclic voltammetry. The cyclic voltametric curve showed symmetric rectangular shape indicating electrical double layer capacitive behavior. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 103-108